Writing Reports for Court : an International Guide for Psychologists Who Work in the Criminal Jurisdiction. - White, Jack (Australian Academic Press, 2015)
Psychologists are increasingly being asked to give evidence in court as expert witnesses, yet for some it can be a harrowing experience. Writing Reports for Court provides essential support for psychologists when preparing a court report and giving evidence.